The Iberian Peninsula in the Iron Age through pottery studies. (Archaeopress Archaeology, 2022)
Seven papers read at the international conference, Interdisciplinary research on pottery from the Iberian Peninsula (Poznań, 2019) deal with various aspects of Iron Age pottery including technology, decoration, chemical and mineralogical properties, commerce and social use through archaeological science and the presentation of ongoing fieldwork.